Towards effective in-service teacher development in Indonesia: Where is the point of departure? - Hidayati Sari (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
In view of the rapid pace of education reforms and the need to improve the quality of teaching, teachers are obliged to engage in continuous professional development (CPD) to improve their pedagogical knowledge and practices. For teachers to be effectively engaged in CPD, programs should be designed not just to expand knowledge and skills, build pedagogical effectiveness, and enhance professionalism, but also to be differentiated to accommodate the diversity of teachers’ needs, skills and knowledge. Professional development is not generic programs designed to fit all teachers’ needs, rather, it is context-embedded. As such, CPD initiatives can only have a positive effect if teachers are able to articulate their actual needs. This paper aims to argue that it is vital that teachers should be given opportunities to articulate their needs to provide robust data that serve as foundations in designing and developing effective CPD. Additionally, other features of effective teacher development programs are also portrayed. These are discussed in relation to the implications they have for teacher professional development and teacher professionalism in Indonesia.